2005
DOI: 10.1097/01.ogx.0000163879.06527.e5
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Prenatally Diagnosed Renal Tumors

Abstract: Several large-scale cohort studies suggest that obese mothers are at increased risk of having infants with neural tube defects and, possibly, other central nervous system (CNS) birth defects. Because obesity and diabetes share similar metabolic abnormalities, a study was planned to determine whether gestational diabetes influences the association between maternal obesity and CNS birth defects. In this population-based case-control study, covering the years 1997 to mid-2000, structured telephone interviews were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 0 publications
1
15
1
6
Order By: Relevance
“…[14] In a study of 28 children with prenatally diagnosed renal tumors (26 with CMN and 2 with Wilms tumor), polyhydramnios were observed in 11 fetuses (39%). [17] Kim et al however, reported a case of CMN occurring in pregnancy with oligohydramnios. [18] CMN most commonly presents as an abdominal mass, but could also manifest with hypertension or hypercalcemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] In a study of 28 children with prenatally diagnosed renal tumors (26 with CMN and 2 with Wilms tumor), polyhydramnios were observed in 11 fetuses (39%). [17] Kim et al however, reported a case of CMN occurring in pregnancy with oligohydramnios. [18] CMN most commonly presents as an abdominal mass, but could also manifest with hypertension or hypercalcemia.…”
Section: Discussionmentioning
confidence: 99%
“…[43] The cellular variant of mesoblastic nephroma has been reported to share cytogenetic features with IFS. Both are associated with polysomies for chromosome 8,11,17,20 as well as translocation t (12;15) (p13;q25), which fuses the E-twenty six variant 6 (ETV 6) or translocation ETS leukemia gene. [1] In a study of five cases of IFS, two of CMN and one of mixed type (CMN and IFS), Adem et al reported that 3 of the 5 cases of IFS had ETV gene rearrangements, but normal copy number of chromosome 11, one case each of IFS, cellular CMN and mixed type had both abnormalities while in the case of classical CMN neither trisomy 11 nor gene rearrangements was found.…”
Section: Discussionmentioning
confidence: 99%
“…Bazı olgularda tümör hücrelerinden prostaglandin veya parathormon benzeri proteinlerin salınımına bağlı olarak hiperkalsemi görülebilir (10). Olguların birçoğunda polihidramniyoz ve preterm eylem olduğu bildirilmiştir (11). Olgumuz da preterm eylem nedeniyle 31. gebelik haftasında doğmuştur.…”
Section: Discussionunclassified
“…Perinatal renal tumors are rare, comprising 5% of all neoplasms arising in the neonate. 11,124 Congenital mesoblastic nephroma is the leading member followed in order by Wilms tumor, rhabdoid tumor, and clear cell sarcoma 11,124,127,129 (Tables 1 and 12). Although hydramnios is common, development of fetal hydrops associated with a renal tumor seldom occurs.…”
Section: Soft Tissue Tumorsmentioning
confidence: 99%
“…[119][120][121][122][123][124][125][126][127][128][129] Factors contributing to the development of hydrops in fetuses with renal tumors include size (a large abdominal mass producing obstruction of the portocaval circulation), high output cardiac failure due to a shunt in a vascular portion of the tumor, or massive hemorrhage into the tumor. 120,122,124,126 Rhabdoid tumors of the kidney tend to be large, rapidly growing, and metastasize early; diaphragmatic elevation with secondary pulmonary insufficiency may occur. 127,128 Clear cell sarcoma of the kidney is the least common malignant tumor of the group that metastasizes to the lungs and bones.…”
Section: Soft Tissue Tumorsmentioning
confidence: 99%